The cardturner : a novel about a king, a queen, and a joker - Sachar, Louis, 1954- (Delacorte Press, 2010)
When his wealthy uncle, a champion bridge player who has lost his vision, asks seventeen-year-old Alton to be a cardturner for him, Alton has no idea how much he will ultimately learn from his eccentric relative. Includes appendix by Syd Fox with information about bridge.